THE EFFECT OF ENVIRONMENTAL UNCERTAINTY, ENTREPRENEURIAL CHARACTERISTICS AND COMMITMENT OF THE GOVERNMENT ON BUSINESS COMPETENCY AND MICRO SMALL BUSINESS PERFORMANCE IN BALIKPAPAN CITY, INDONESIA - Darya, I Gusti Putu (APPS Publications, 2020)
This study is aimed to analyze the influence of environmental uncertainty, entrepreneurial characteristics and government commitment to business competence and the performance of small micro businesses in Balikpapan city. This study involves 34 villages, each of which was taken as a sample of 5 people per village of micro and small business operators, and as many as 136 responses were collected. Data processing used AMOS 6.0, and the result was that environmental uncertainty did not directly affect the performance of micro-small businesses but through business competence. Entrepreneurial characteristics did not affect business competence but competence influenced the performance of micro small businesses. Meanwhile, the government’s commitment directly or indirectly influenced through business competence on the performance of micro small businesses. It is recommended that micro-small entrepreneurs can always improve their competency through entrepreneurship skills training so they can face uncertainty.